Fragilities and potentialities in the humanization attendance process in the intensive care unit: a qualitative and dialectic based-study - Leandro Barbosa de Pinho; Silvia Maria Azevedo dos Santos (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
This study attempts to unveil difficulties and potentialities in the process of humanization attendance in the intensive care unit, from the speech of the intensive nursing, the perception of family members and interned patient. It is a qualitative, dialectic-based study involving 7 nurses, 4 family members, and 1 patient of the Adult ICU in the University Hospital of the Federal University of Santa Catarina, Brazil.
We evidence that the fragilities and potentialities in the humanization care process in the ICU involve a set of premises and factors, that if relate dialectically, going since the necessities most caregiver subjective and the well-taken care of being, until more structural dimensions, that if they around locate of the context and the spaces of performance. We think that reflection of the context of intensive attendance can help in the transformation of the reality, where professional that they take care of and well-taken care of people are in tunning, share experiences and limitations and, more of the one than this, they value the human potentials.